Distinct response patterns of endothelial markers to the BNT162b2 mRNA COVID-19 booster vaccine are associated with the spike-specific IgG antibody production - Castro-Robles, Beatriz; Cimas, Francisco J.; Arias-Salazar, Lourdes; Ontañón, Jesús; Lozano, Julia; López-López, Susana; Andrés-Pretel, Fernando; Requena-Calleja, María Ángeles; Mas, Antonio; Serrano-Heras, Gemma; Segura, Tomás; Solera, Javier (Frontiers in Immunology, 2025)
IntroductionDespite the efficacy and safety of SARS-CoV-2 vaccines, inflammatory and/or thrombotic episodes have been reported. Since the impact of COVID-19 vaccines on the endothelium remains uncertain, our objective was to assess endothelial activation status before and 90 days after the third dose of the BNT162b2 mRNA COVID-19 vaccine.MethodsA prospective longitudinal study was conducted at University General Hospital of Albacete, involving 38 healthy health-care workers. Serum levels of endothelial markers (endocan and sVCAM-1) and spike S1-specific IgG antibodies were determined before and at 7, 15, 24 and 90days following vaccination. To analyze each participant´s individual response, we calculated relative increases/decreases (delta values) in endothelial markers and antibodies concentrations compared to their pre-vaccination levels.ResultsWe identified two significantly distinct profiles of endothelial markers response, characterized by either increased or decreased serum levels of endocan and sVCAM. Incremental and decremental response groups did not differ in terms of age, sex, cardiovascular risk factors, previous SARS-CoV-2 infection and influenza vaccine co-administration. However, these responses were significantly associated with the relative spike-specific antibody production. Specifically, the greatest relative increase in antibodies was found in the decremental responders. Additionally, the higher delta antibody production was observed in non-previously infected individualsConclusionAdministration of the BNT162b2 booster vaccine triggered a non-homogenous response of endothelial function markers among the study participants. Our findings improve the understanding of individual responses to the mRNA COVID-19 booster vaccine, which could be useful in assessing the need for booster doses, particularly in population at risk of vascular complications.